Sampling theory - Raj, Des. (New York : McGraw-Hill Book Company, 1968)
The author aims to provide an up-to-date account of sampling theory as it has been developed during the last three decades. The book is intended for students who want to learn sampling theory at an intermediate level and for research workers who need to be familiar with the latest developments in the subject.
Includes bibliographical references and index.
rpm 09/07/2018
Loans
Keywords: Sampling Theory; Sampling (Statistics).; Signal processing